Ammonium fluoride roasting and water leaching of leucoxene concentrates to produce a high grade titanium dioxide resource (of the Yaregskoye deposit, Timan, Russia); Hydrometallurgy; Vol. 210 - Perovskiy I. A. Igor; Burtsev I. N. Igor; Ponaryadov A. V. Alexey; Smorokov A. A. Andrey Arkadievich (2022, 2022)
Title screen